The effect of political trust and trust in European citizens on European identity. Issue 2 (30th September 2015) - Hooghe, Marc; Verhaegen, Soetkin
Abstract : In the literature, two approaches toward the development of a European identity can be distinguished. Society-based approaches assume that the most important foundation for the development of a European identity is trust toward other European citizens as this allows Europeans to identify with the European Union as a community of citizens and values. The institutional approach, on the other hand, assumes that a shared European identity is predominantly based on trust in political institutions. In this paper, we use the results of the IntUne Mass Survey 2009 ( n =16, 613 in 16 EU member states) to test the relationship between social and political trust on the one hand, and European identity on the other. The results suggest that trust in other European citizens is positively associated with European identity, but trust in the European political institutions has a stronger relation with European identity. This could imply that efforts to strengthen European identity cannot just rely on a bottom-up approach, but should also pay attention to the effectiveness and the visibility of the EU institutions and the way they are being perceived by European citizens.